Efficient removal of heavy metals from polluted water with high selectivity for Hg(ii) and Pb(ii) by a 2-imino-4-thiobiuret chemically modified MIL-125 metal–organic framework. Issue 23 (13th April 2021) - Adly, Mina Shawky; El-Dafrawy, S. M.; Ibrahim, Amr A.; El-Hakam, S. A.; El-Shall, M. Samy
Abstract : A highly porous adsorbent based on a metal–organic framework was successfully designed and applied as an innovative adsorbent in the solid phase for the heavy metal removal. Abstract : A highly porous adsorbent based on a metal–organic framework was successfully designed and applied as an innovative adsorbent in the solid phase for the heavy metal removal. MIL-125 was densely decorated by 2-imino-4-thiobiuret functional groups, which generated a green, rapid, and efficacious adsorbent for the uptake of Hg(ii ) and Pb(ii ) from aqueous solutions. ITB-MIL-125 showed a high adsorption affinity toward mercury(ii ) ions of 946.0 mg g −1 due to covalent bond formation with accessible sulfur-based functionality. Different factors were studied, such as the initial concentration, pH, contact time, and competitive ions, under same circumstances at the room temperature. Moreover, the experimental adsorption data were in excellent agreement with the Langmuir adsorption isotherm and pseudo-second order kinetics. At a high concentration of 100 ppm mixture of six metals, ITB-MIL-125 exhibited a high adsorption capacity, reaching more than 82% of Hg(ii ) compared to 62%, 30%, 2%, 1.9%, and 1.6% for Pb(ii ), Cu(ii ), Cd(ii ), Ni(ii ), and Zn(ii ), respectively.